Hydrothermal Synthesis of MoS2/rGO Heterostructures for Photocatalytic Degradation of Rhodamine B under Visible Light - Thi Thuy Trang Phan; Thi Thanh Huong Nguyen; Ha Tran Huu; Thanh Tam Truong; Le Tuan Nguyen; Van Thang Nguyen; Vy Anh Tran; Thi Lan Nguyen; Hong Lien Nguyen; Vien Vo (My University, 2021)
Hydrothermal Synthesis of MoS2/rGO Heterostructures for Photocatalytic Degradation of Rhodamine B under Visible Light
Keywords: MoS2/rGO